A handbook for Qur'anic based lifelong learning module for the elderly - Nik Abdullah, Nik Md. Saiful Azizi; Fatah Yasin, Raudlotul Firdaus; Abdullah, Mohamad Ridhuan; Nordin, Ossman; Abdul Hadi, Ahmad Zulfiqar Shah; Abd Samad, Mohd Shamsul Hakim Abd Samad (Islamic Book Trust, 2024)
This handbook offers a Qur’ānic-based lifelong learning module tailored for the elderly, focusing on spiritual growth and knowledge retention aligned with Islamic teachings. It provides a comprehensive framework that accommodates the unique physical, cognitive, and emotional needs of elderly learners, fostering an inclusive and enriching learning environment. Essential for educators, caregivers, and scholars, this handbook empowers the elderly to engage in continuous learning, grounded in the Qur’ān and Ḥadīth. It’s a valuable resource for anyone committed to honoring the wisdom of the elderly and supporting their lifelong pursuit of knowledge within an Islamic context.